2019
DOI: 10.3390/ijerph16245081
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedents and Consequences of Travelers’ Well-Being Perceptions: Focusing on Chinese Tourist Shopping at a Duty Free

Abstract: The purpose of this study was to explore the antecedents and consequences of travelers' well-being perceptions in the context of a duty-free shop. For this, data were collected from 742 Chinese tourists who purchased goods at duty free shops while traveling in Korea within the past year using an online survey company's system in China. The results indicated that pragmatic, hedonic, and sociability experiences have a positive influence on travelers' well-being perceptions. In addition, travelers' well-being per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 93 publications
(137 reference statements)
2
18
1
Order By: Relevance
“…The tourism research has concerned itself with whether the future tourist behavior can be anticipated from the tourist satisfaction model [83]. Along these lines, satisfaction is viewed as a precursor variable of the word-of-mouth [91,92]. The word-of-mouth (WOM) is characterized as "casual, individual-to-individual correspondence between an apparent non-business communicator and a recipient with respect to a brand, an item, a business, or a service" [10,93].…”
Section: Word-of-mouthmentioning
confidence: 99%
“…The tourism research has concerned itself with whether the future tourist behavior can be anticipated from the tourist satisfaction model [83]. Along these lines, satisfaction is viewed as a precursor variable of the word-of-mouth [91,92]. The word-of-mouth (WOM) is characterized as "casual, individual-to-individual correspondence between an apparent non-business communicator and a recipient with respect to a brand, an item, a business, or a service" [10,93].…”
Section: Word-of-mouthmentioning
confidence: 99%
“…This type of policy reduces customs duty taxes, valued added tax, and consumption tax (Bouët et al, 2012). Duty-free policies also represent a typical tax policy to spark tourism consumption, meant to encourage tourists to shop in destinations and to consume products (Kim et al, 2019). Studies have shown that a duty-free policy can enhance individuals' travel intentions, tourism spending, and tourism revenue.…”
Section: Duty-free Policiesmentioning
confidence: 99%
“…The literature on tourist destinations' duty-free policies has largely focused on qualitative analyses of policy implementation and associated shortcomings, demonstrating the role of duty-free policies in promoting travel intentions (e.g., Dimanche, 2003;Lin and Chen, 2013;Kim et al, 2019;Martín et al, 2019). However, there has been less discussion of the specific mediating mechanisms (e.g., consumer perceived value) through which duty-free policies affecting travel intentions, and there is a lack of behavioral theory (e.g., functional theory of counterfactual thinking) to explore the moderating variables.…”
Section: Introductionmentioning
confidence: 99%
“…It can be defined as the extent to which a certain consumer good/service provides the overall perception of the QOL [12]. In other words, the level of QOL is a crucial standard in determining WBP [13]. For instance, if senior tourists perceive that their QOL is increased, then they have high levels of WBP.…”
Section: Wellbeing Perception (Wbp)mentioning
confidence: 99%